FEATURES OF AN INFECTIOUS ENDOCARDITIS IN INJECTION «SALT» ADDICTS - M. V. Stolbova; U. V. Liscova; N. E. Artemova; R. I. Saifutdinov; O. V. Bugrova (Архивъ внутренней медицины)
The purpose of the research was studying of features of clinic, course, medical tactics and outcomes of infectious endocarditis in 25 patients suffering from “salt” drug addiction. Materials and methods: we examined 25 patients with infectious endocarditis, the host “salt” intravenously. To verify the diagnosis in addition to standard studies of blood, urine, sputum, was performed transthoracic EchoCG, x-ray study of the chest (twice, at admission and before discharge of the patient from the hospital). For certain indications used diagnostic fiber-optic bronchoscopy and computed tomography of the lungs, consulted a neurologist, cardiologist, infectious disease. Results and discussion: 84% of patients diagnosed with HIV. The acute course of the disease and presence of accompanying pathology of organs and systems was observed in the majority of patients, with a predominance of neurological changes (88%). Typical meager cardiac symptoms (noise in the region of the heart were heard in 12% of patients), frequent lung as a result of pulmonary embolism (64%). Identified infectious agents (in most cases Staphylococcus aureus -32%), the defeat of the heart valves according to the EchoCG (in 72% of patients vegetation on tricuspid valve with varying degrees of regurgitation). The choice of antimicrobial medicines was optimized (cephalosporins I-III generation, aminoglycosides, vancomycin). The positive outcome of a disease was observed in 84% of patients, mortality was 16%. Conclusions: for infectious endocarditis injecting a “salt” of the drug revealed the following: acute disease; pronounced General symptoms, atypical clinical picture, involvement of the heart valves, lungs result in pulmonary embolism, early development of multiple organ failure, high mortality. In comparison with injection drug users who inject other drugs, “salt” addicts are characterized by the frequent development of infectious endocarditis, which is apparently connected with the influence of “salt” on the immune system and joining the bright and varied neurological symptoms.